Vascular calcification and plasma levels of osteopontin in patients with chronic kidney disease who are treated by program hemodyalisis - V. A. Vizir; A. V. Abramov; A. S. Sadomov; E. G. Ovska (Zaporožskij Medicinskij Žurnal)
Aim. To examine vascular calcification and plasma levels of osteopontin in patients with chronic kidney disease who are treated by program hemodyalisis